1994
DOI: 10.1007/bf01499592
|View full text |Cite
|
Sign up to set email alerts
|

Racial prejudice in the Canadian legal system: Juror decisions in a simulated rape trial.

Abstract: The effects of defendant and victim race and the impact of judicial instructions on defendant verdict were examined using a simulated videotaped rape trial. Subjects were 243 Canadian university students randomly assigned to one of eight conditions. Subjects were asked to assume the role of juror and to view a videotape of a simulated rape trial. The results indicated that the defendant's overall attractiveness or "positive appeal" was the best predictor of defendant guilt, above and beyond defendant race. Nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…It is thought that having individuals discuss a case may increase each person's accountability to follow the law, or adhere to judicial instructions to set aside personal biases (Kerwin & Shaffer, 1994). Bagby et al (1994) suggest that the process of deliberating ''helps to realign the juror with the facts and rules of the case'' (p. 348). On the other hand, the process of debating and discussing the factors of a case may raise issues that were individually ignored, and can place emphasis on extralegal evidence that may not have been identified as salient by the individuals alone.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that having individuals discuss a case may increase each person's accountability to follow the law, or adhere to judicial instructions to set aside personal biases (Kerwin & Shaffer, 1994). Bagby et al (1994) suggest that the process of deliberating ''helps to realign the juror with the facts and rules of the case'' (p. 348). On the other hand, the process of debating and discussing the factors of a case may raise issues that were individually ignored, and can place emphasis on extralegal evidence that may not have been identified as salient by the individuals alone.…”
Section: Studymentioning
confidence: 99%
“…Researchers employing the jury simulation method have found that a variety of defendant characteristics (e.g. socioeconomic status, ethnicity, religion, race, and attractiveness) can bias mock jurors' judgements and, in turn, influence decisions of guilt and/or sentencing (Albonetti, 1997;Bagby, Parker, Rector, & Kalemba, 1994;Frederick, 1987;Perez et al, 1993). An underlying assumption in jury bias research is that individual beliefs and attitudes can affect judgements made in legal situations, such that ''there may be individual differences in the way jurors attend to, organize, and retrieve evidentiary information'' (Furnham & Alison, 1994, p. 37).…”
mentioning
confidence: 99%
“…African Americans, as a discriminated-against minority group, have a long history of being abused by the criminal justice system (e. g., Bagby, Parker, Rector, & Kalemba, 1994;Barnes & Kingsnorth, 1996;Bell, 1973;LaFree, 1980;Perez, Hosch, Ponder & Trejo, 1993;Peterson & Hagan, 1984; but see Fein, Morgan, Norton, & Sommers, this issue, and Skolnick & Shaw, this issue, for discussions of "reverse discrimination" effects). These abuses include higher rates of arrest, of being charged with a crime, of being convicted, and of being sentenced, as well as longer sentences (cf.…”
Section: Debunking Racementioning
confidence: 96%
“…Due to optimal representation point allocations and the fact that Bayes risk performance does not get worse when the number of quantization levels K is increased [18], a white decision maker would perform worse than a black decision maker when dealing with blacks and a black decision maker would perform worse than a white decision maker when dealing with whites, judging quality by expected Bayes risk. Under appropriate values of decision maker preferences, c 01 and c 10 , the decision making model generates the in-race bias or out-of-race bias that has been observed empirically [6], [22]- [24].…”
Section: Price Of Segregationmentioning
confidence: 99%
“…First we consider a single decision maker, aiming to understand the bias based on race, the so-called racial profiling that has been observed in several decision-making scenarios of the type described, including foul calls by National Basketball Association (NBA) referees, arrests for minor offences by police, searches of stopped vehicles by police, and jury decisions [6], [22]- [24]. Our model provides an explanation that does not invoke invidious motive by the decision maker.…”
Section: Introductionmentioning
confidence: 99%